Strategi Pengembangan Wisata Daerah (Studi tentang Penataan Infrastruktur di Agrowisata Belimbing Karangsari Kota Blitar) - Budi Santoso; Eka Askafi (Universitas Islam Kadiri, 2020)
This time Blitar City has already had a national tourism icon, which is Bung Karno’s Graveyard. In order to support the development of this main tourism object, surely it must be supported by another tourism object. Unluckily, there are not many tourism objects which can support Bung Karno’s Graveyard, so tourists can’t feel at home and needn’t to stay longer in Blitar City. Blitar city is not a large City and has limited natural resources too, so nature tourism is not a potency. Therefore, Blitar City’s Government tries to develop supporting tourism objects from the existance Blitar City’s potency. Karangsari star fruit is such an existing potency of agricultural sector in Blitar City. Blitar City’s Government does not want only stay on the production of star fruit and its processing products, but star fruit is also become anAagro-tourism which certainly has a wider impact and gives a multiplier effect on Blitar City’s economy. Finally, this Agro-tourism becomes a tourist object which is expected to support the tourism area of Bung Karno’s Graveyard. In order to support the development of this Agro-tourism, surely needs a planning to support and managing the Agro-tourism area infrastructure which can be used as a macro guideline in area management. The Blitar City’s Government has been trying to repair the residential environment of surrounding location. It can be seen from the existing programs which are given related to environmental quality improvement. The existing programs include the Urban Village Community Empowerment Program (PPMK). Nevertheless, the program has not provided significant results for the area of Agro-tourism area yet. Therefore, it is necessary to reformulate the proper manufacturing of the Agro-Tourism of Karangsari Starfruit area through infrastructure arrangement of it’s location. Based on the prior conditions, so it was carried out a research on the development of tourism in the study area concerned with infrastructure management in Agro-tourism of Karangsari Starfruit of Blitar City. This study has purpose to describe the infrastructure management, determine internal and external factors and analyze development strategies in Agro-tourism of Karangsari Starfruit, Blitar City. The research process begins by identifying the characteristics of the Agro-tourism Karangsari Starfruit area. Then conducted an analysis of internal and external factors. The research method which used is descriptive qualitative, with sources of data from interviews, observations, and reviews of several literatures. The data analysis are used SWOT technique. From the results of the IFAS and EFAS analysis, strategies that are considered which have urgent priorities will be found. The results of this research indicate that the main strategies that must be carried out for the development of Agro-tourism of Karangsari Starfruit in Blitar City are : 1).Developing the tourism’s interest, especially artificial tourism by utilizing a sports field which located in westside of the Agro-tourism area, 2).Providing of a new access point from the southside to the Agro-tourism area, 3).Developing of circulation in the star fruit garden area used the boardwalk concept, 4).Creating a special website for Agro-tourism of Karangsari Starfruit. This research is expected to be able to give suggestion to the Government in order to develop regional tourism in Agro-tourism of Karangsari Starfruit in Blitar City.